The relationship between distress tolerance and life satisfaction among young adults in Saudi Arabia - Abd Ellatif Elsayed, Hala; Aleriani, Fatemah (Frontiers in Psychology, 2024)
Purpose: This study examined the relationship between Distress Tolerance, defined as the individual's ability to withstand psychological stress or endure negative emotions, and Life Satisfaction, the cognitive component of the individual's subjective well-being, among Saudi young adults aged 20 to 30. The study aimed to understand the overall scores of distress tolerance, life satisfaction, and gender differences in these variables.Method: Online questionnaires were distributed to 348 participants selected based on inclusion/exclusion criteria, using self-report scales: the Distress Tolerance Scale (DTS) and the Satisfaction with Life Scale (SWLS). The sample consisted of 77 males and 271 females, with a mean age of 1.8793 years (SD = 0.81931). Data were analyzed using the SPSS program.The findings supported our hypotheses that (1) Saudi young adults have high overall scores of distress tolerance and life satisfaction, (2) there is a significant positive correlation between distress tolerance and life satisfaction, (3) there are no significant differences between males and females regarding overall distress tolerance and life satisfaction levels, although (4) a significant gender difference was found in the emotional regulation subscale of DTS. A linear regression analysis also showed that distress tolerance significantly predicts life satisfaction.Distress tolerance and life satisfaction are positively associated among Saudi young adults, with no significant gender differences in overall levels. However, differences in specific subscales, such as emotional regulation, warrant further investigation. These findings provide valuable insights for interventions to enhance this population's well-being.